The spillover effect of tax system improvement: the evidence from accounting information quality - Junxiong Fang; Ning Chen; Huihua He; Qi Fu (China Journal of Accounting Studies)
This paper examines whether improvements in a firm’s tax system impose positive spillover effects on its accounting system and accounting information quality. Using China’s 2014 Tax-paying Credit Rating system, we find that A-rated firms exhibit lower discretionary accruals and improved accounting quality. These results remain robust after applying propensity score matching (PSM) and difference-in-differences (DID) model, restricting the sample to firms with high disclosure quality or adopting the Golden Tax Phase III system, and using alternative measures Furthermore, the effects are more pronounced for firms with weak internal and external governance mechanisms. Overall, our findings highlight a positive spillover from tax system improvements to accounting information quality, offering empirical support for the Tax-paying Credit Rating system as an effective tool for both tax enforcement and financial governance enhancement.